Penyebab dan Larangan Kepemilikan Tanah Absentee di Indonesia - rizi, Alfa; Syaputra, Didi; Roselino, Veronika; Putra, Suria Ade; Sukur, ABD; Adnan, Indra Muchlis (Indra Institute Research & Publication, 2024)
The government has carried out reforms in many ways through the land reform program which regulates land ownership and the legal relationship between the landowner and the object of the land, in order to create a society that has a prosperous and productive life in advancing a national community economy and food security. One of these efforts is the prohibition of land ownership, especially agricultural land which has been regulated in a composition of law article 10 paragraph 1 of the UUPA. With this article, the government expects the owner of the land or land to work on it himself. So that productivity can run optimally, with people who have been educated regularly and have high discipline. However, in fact, in the field in some villages, there are still many people who control absentee land and the community interprets all forms of rules regarding absentee land ownership is very ineffective. Therefore, the author conducted this study with the aim of finding out what causes the occurrence of absentee land ownership and why absentee land ownership is prohibited in Indonesia. Where this research uses a literature method where the reference sources come from books, journals, previous articles. So as to produce a study in which the cause of absentee land ownership in Indonesia are based on several factors, namely public awereness factor that are still too low, community knowladge that is still weak, culture, legal factors, facilities, law enforcement and economy. In addition, the ban on absentee land ownership is carried out to prevent land ownership without a cultivation process so that the agricultural land becomes scrub and abandoned.